2021
DOI: 10.2147/mder.s298207
|View full text |Cite
|
Sign up to set email alerts
|

Avitene™ Microfibrillar Collagen Hemostat for Adjunctive Hemostasis in Surgical Procedures: A Systematic Literature Review

Abstract: Adequate hemostasis during surgical procedures is essential for successful patient outcomes and reduced healthcare resource utilization. Topical hemostatic agents can act as catalysts for the clotting cascade or as a scaffold to promote platelet activation or aggregation. Although an ever-increasing number of topical absorbable hemostatic agents are now available for perioperative use, health care providers are disadvantaged by the lack of comparative data on feasibility, clinical effectiveness, advantages, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…All MCF samples have a good hemostatic ability, with a much shorter clotting time than that of the control sample. It could be suggested that when in contact with blood, the platelets were adhered to collagen fibrin and then they were aggregated 3 . These results have a high accuracy with RSD < 2% and there were significant differences in clotting time between experimental groups ( P < 0.001).…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…All MCF samples have a good hemostatic ability, with a much shorter clotting time than that of the control sample. It could be suggested that when in contact with blood, the platelets were adhered to collagen fibrin and then they were aggregated 3 . These results have a high accuracy with RSD < 2% and there were significant differences in clotting time between experimental groups ( P < 0.001).…”
Section: Resultsmentioning
confidence: 85%
“…In modern surgery, passive hemostatic agents such as microfibrillar collagen, collagen sponges, collagen membranes, oxidized regenerated cellulose, gelatin sponges and mesoporous polysaccharide spheres are topical hemostatic agents that have been commonly used owing to their convenience, fast hemostasis, immediate availability, ease of use, cost effectiveness and storage at room temperature. [1][2][3][4][5][6][7] These hemostatic agents work by interacting with a bleeding surface, absorbing fluid and promoting platelet activation and aggregation to form blood clots. 8 Among passive hemostatic agents, collagen has many applications in various forms, including microfibers, sponges, membranes, powders, sheets and pads.…”
Section: Introductionmentioning
confidence: 99%
“…11 A similar temporary embolic agent composed of microfibrillar collagen works by activating platelet aggregation and the formation of fibrin to enhance hemostasis. 12 Drug-eluting beads (DEBs) are a newer generation of microspheres that have the capability to be loaded with chemotherapeutic agents to provide localized tumor treatment. The drug-loading capacity of these particles utilizes a negatively charged ionic group to bind to positively charged chemotherapy drugs (►Fig.…”
Section: Methodsmentioning
confidence: 99%
“…11 A similar temporary embolic agent composed of microfibrillar collagen works by activating platelet aggregation and the formation of fibrin to enhance hemostasis. 12…”
Section: Methodsmentioning
confidence: 99%
“…The structural and signaling role of collagen makes it an ideal biomaterial for applications in the field of biomedical [7], cosmetics [8], nutraceuticals [9] and pharmaceuticals. In addition, natural properties like hemostatic activity [10], biodegradability [11] and cross-linking ability of collagen find a wide application in the drug delivery systems [12][13][14]. Gelatin, a biopolymer obtained by partial hydrolysis of collagen fibres has major applications in confectionery, food, pharmaceutical, medical, cosmetic products [15].…”
Section: Introductionmentioning
confidence: 99%